ANALISIS PENERAPAN IMBALAN PASCAKERJA PADA KARYAWAN PT. MOY VERONIKA - ., Monalisa; Runtu, Treesje; Lambey, Robert (Universitas Sam Ratulangi, 2018)
Employee Benefits consist of short-term benefit, long-term benefit, post-employment benefit and severance pay. Regarding the ease and also the economic safety of the employee, company is obligated to prepare and allocate the post-employment benefit and also declare their will to pay at the end of the employee’s work. This research aims to analyze the implementation of post-employment benefit on the employees of PT. Moy Veronika based on PSAK 24 and UUK No. 13 Tahun 2003. The method used in this research is qualitative descriptive research method. The result of this research shows that the implementation of the post-employment benefit by PT. Moy Veronika hasn’t been in accordance with PSAK 24, in which the factor that caused the absence of recording of the post-employment benefit transaction is owner’s ignorance in reserving the post-employment benefit due to the their kinship with the employees and the implementation of distributing the post-employment benefit in PT. Moy Veronika is already in accordance with UUK No. 13 Tahun 2003, in which the termination of work occurs due to 1) Resignation; 2) Death; 3) Pension; 4) Prolonged illness/disability, the company has fulfilled its obligation in distributing the postemployment benefit.Keyword : post-employment benefit